Developing packaging quality and marketing strategy for the product of Kopi Arabika Ran-Aini - Shakila Panita; Wulan Dewi; Zikril Hakim; Randi Syafutra (Universitas Muhammadiyah Magelang, 2024)
The aim of the Community Service (PkM) is to develop packaging quality and marketing strategies for Ran-Aini Arabica Coffee products. This PkM was carried out using two methods in stages, namely: unstructured interviews and mentoring. The results of the interviews show that Ran-Aini Arabica Coffee products are not developing well due to two obstacles, namely unattractive product packaging and limited product marketing. This is the basis for the PkM Team to immediately carry out assistance. The assistance provided by the PkM Team is in the form of assistance in making product packaging and assistance in marketing products via digital platforms. In the end, through this PkM, Ran-Aini Arabica Coffee products have attractive packaging, and sales accounts on WhatsApp and Instagram digital platforms are more effective marketing media.